Filtena: integra??o de antenas e filtros de RF e microondas reconfigur?veis - Silva, Lui?s Gustavo da (2014)
This work is focused on the development of innovative technologies for radio frequency filters. Initially, the design and optimization, using evolutionary strategy algorithm, of a tri-band filter for cellular systems is presented. Next, we describe the development of novel structures called filtenna, which integrate reconfigurable filters, electrically and optically, and antennas for frequencies up to 23GHz. The project methodology is based on four steps: Analytical calculations; optimization and numerical simulations; prototype fabrication; experimental characterization. Numerical simulations were carried out using the pieces of software Agilent Genesys, ANSYS Designer e ANSYS HFSS. Prototype fabrication and characterization were realized in the laboratories WOCA and ICC-Hardware from Inatel. Excellent agreement between theoretical and measured results has been observed for the three proposed filters.